Perlindungan Hukum Konsumen Terkait Jual Beli Tiket Pesawat Secara Online - Moh Jihad Labetubun; Merry Tjoanda; Muchtar Anshary Hamid Labetubun (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: Development of transportation, especially air transportation, is now growing very rapidly, supported by today’s technology, this also causes various kinds of problems, especially in buying and selling airplane tickets online, many complaints from consumers such as delays in confirming e-tickets that have been purchased, unilaterally increase the interests of the travel party which is certainly very detrimental to the consumer.Purposes of the Research: The obectives of this research are: to find out and analyze business actors in selling airplane tickets online is against consumer losses. This research includes normative legal research conducted with a legal  and conceptual approach. Data collection techniques by means of literature study, documents study. Methods of the Research: The type of research is normative juridical, with two approaches, namely the conceptual approach and the legal approach.Results of the Research: Bassed on the result of the study, it shows that consumer protection in buying and selling airplane tickets online has not been running properly because the Consumer Protection Act can be implemented because business actors are still obligated, prohibited and have consumen rights. Especially in providing correct, clear and honest information. This is because business actors are solely looking for their own profit. Consumer results get guarantees for consumer rights. The responsibility of the business actor or seller here is to make compensation based on Article 19 parragraph (1) of Law Number 8 of 1999 concerning Consumer Protection.